2006
DOI: 10.1111/j.1939-165x.2006.tb00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of static telepathology in veterinary diagnostic cytology

Abstract: Telepathology by e-mail provides acceptable efficacy and a faster turnaround time than post and can be applied to veterinary diagnostic cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…50 In contrast to DP, static telepathology consists only of single images taken manually with a camera mounted on a light microscope in a quite time-consuming manner, while dynamic telepathology describes a quite cumbersome real-time streaming of visual fields by 1 active observer to a remote passive observers. 42 In veterinary pathology, static telepathology has been shown to achieve acceptable diagnostic accuracy and may currently be more common because of the affordability of the technical equipment. 42 Ergonomics Improved ergonomics may be another reason to integrate DP systems into the routine pathology workflow, as reported by Thorstenson et al 67 Based on a questionnaire, they showed that almost all pathologists experienced an improvement of ergonomics after implementation of DP into the diagnostic routine.…”
Section: Telepathologymentioning
confidence: 99%
See 1 more Smart Citation
“…50 In contrast to DP, static telepathology consists only of single images taken manually with a camera mounted on a light microscope in a quite time-consuming manner, while dynamic telepathology describes a quite cumbersome real-time streaming of visual fields by 1 active observer to a remote passive observers. 42 In veterinary pathology, static telepathology has been shown to achieve acceptable diagnostic accuracy and may currently be more common because of the affordability of the technical equipment. 42 Ergonomics Improved ergonomics may be another reason to integrate DP systems into the routine pathology workflow, as reported by Thorstenson et al 67 Based on a questionnaire, they showed that almost all pathologists experienced an improvement of ergonomics after implementation of DP into the diagnostic routine.…”
Section: Telepathologymentioning
confidence: 99%
“…42 In veterinary pathology, static telepathology has been shown to achieve acceptable diagnostic accuracy and may currently be more common because of the affordability of the technical equipment. 42 Ergonomics Improved ergonomics may be another reason to integrate DP systems into the routine pathology workflow, as reported by Thorstenson et al 67 Based on a questionnaire, they showed that almost all pathologists experienced an improvement of ergonomics after implementation of DP into the diagnostic routine.…”
Section: Telepathologymentioning
confidence: 99%
“…Given that cytopathologists routinely assess slides of poor cellularity without the benefit of tissue architecture, the limitations of static telecytology do not invalidate its potential utility. Previously, practitioners needed to have costly equipment, including a microscope with a camera, but this is no longer a vital component . Access has expanded to nearly any person with a camera phone ± a scope adaptor …”
Section: Introductionmentioning
confidence: 99%
“…There are advantages to telecytology, particularly for practices that are not equipped with their own in‐house clinical pathology laboratory, which are the majority, or for those outside greater metropolitan areas with time‐limited options for transferring glass slides to a referral laboratory. The turnaround time for diagnosis is reduced if clinicians submit electronic images rather than sending slides in the mail or through a courier . Faster turnaround is anticipated to promote higher quality patient care and potentially more frequent submissions.…”
Section: Introductionmentioning
confidence: 99%
“…The authors conclude that this system worked adequately for routine use [33]. Other examples of static-image cytology have shown excellent accuracy and reproducibility among observers in a variety of organ systems and even for use in veterinary cytology practice [34,35,36,37]. …”
Section: Telediagnosis/teleconsultationmentioning
confidence: 99%